Assessment of periodontal health among the rural population of Moradabad, India - Manu Batra; Pradeep Tangade; Devanand Gupta (Wolters Kluwer Medknow Publications, 2014)
Introduction: Oral health is an integral component of general health and is essential for well-being. India is one of the most populated countries in the world and majority of them resides in rural areas. Moradabad is one of the oldest cities of Uttar Pradesh with diverse culture and beliefs. Aim: The aim was to evaluate the periodontal health status of the rural Moradabad population. Materials and Methods: A representative transversal study on 550 adults aged 20-49 years of rural Moradabad was conducted from February 2011 to June 2011. The survey was carried out using a self-designed questionnaire. Periodontal health was assessed using WHO criteria (1997). Results: Overall the prevalence of periodontal diseases among study subjects was overall 91.6%. Males had a higher prevalence of periodontal disease (93.8%) as compared to females (89.5%). Out of total subjects 37.8% had Community Periodontal Index (CPI) score 4 and 32.5% had score 3. About 7.3% of subjects had loss of attachment (LOA) with 20.2% of them having LOA score 1. Statistically, there was a significant difference (P < 0.001) among the number of subjects having different CPI and LOA scores. In a multivariate binary logistic model with age > 35 years, smoking, tobacco chewing (independent risk factors) were significantly associated with CPI > 2 (dependent variable) (P < 0.05). Conclusion: The current periodontal health status of rural adult population of Moradabad city can be attributed to low literacy along with socio economic status and oral habits. To improve the periodontal health status of the rural population of Moradabad, it is suggested that a community-based approach can be designed.